Reflections on ethical issues: a study of how urban women dealt with impoverishment - Muzvidziwa, Victor N. (2016)
This paper argues for the pursuit of social science research as a moral enterprise. The paper builds on the experience gained by the author during a 14-months post-graduate fieldwork project in a provincial town of Masvingo in southern Zimbabwe. Central to the research process is the need for participation, integrity and responsibility on the part of researchers. In deciding what is appropriate behaviour by the researcher there is need to take into account both local and global expectations and demands. Good and effective researchers should possess what Adjibolosoo terms positive human factor attributes such as integrity, loyalty, accountability, responsibility, motivation, honesty, wisdom, vision, dedication, commitment, creativity, skills, knowledge,understanding and trustworthiness. Ethically driven research entails establishing caring relationships and a concern for the well being of respondents. The paper also raises issues pertaining to the problematic of a man studying women, the politics of fieldwork and research as a political process, how a researcher positions himself/herself in order to engage policy makers and the powerful. Research it is argued should be founded on the basis of mutual respect. This means the avoidance of deception, dishonesty and pretence in fieldwork settings. A researcher without a caring ethic will find it hard to understand fieldwork challenges and observations.Ethical caring is the foundation on which trust between researcher and respondents is built in the course of research.